Floral trait preferences of butterflies in Singapore - Fung, Louisa May (Nanyang Technological University, 2021)
Most butterfly species do not forage on all flowers available, but visit specific flowers displaying certain traits. While butterfly ecological and morphological traits have been linked to flower specialisation, the flower traits associated with flower specialisation in this same system have not been explored. I hypothesise that butterfly feeding interactions can be predicted by flower trait groups, rather than just plant species alone. My study therefore aims to use the floral traits of butterfly-attracting plants to study flower preferences of Singaporean butterflies. My results show that flowering plant species may not form overall trait group clusters, but when traits are analysed individually or grouped with similar trait types, clearer trait preferences can be observed. Community-level preferences for morphology traits, flower shape, visible colour reflectance and nectar volume are identified, with an overall preference for flowers with smaller morphological features, tubular shapes, higher yellow reflectance, and flowers with low-no visible volumes of nectar. Some specific preferences were also discovered, with butterflies of the family Papilionidae and some Nymphalidae species preferring flowers with longer corolla tubes and larger inflorescence areas. Since butterflies of similar families showed similar flower preferences, family-level conservation plans can be devised. The floral trait preferences identified can be used to select suitable flowering plant species for landscape management targeted to butterfly conservation.